Adenocarcinoma at the gastroesophageal junction. (29th September 2014) - Al‐Haddad, Sahar; Chang, Andrew C.; De Hertogh, Gert; Grin, Andrea; Langer, Rupert; Sagaert, Xavier; Salemme, Marianna; Streutker, Catherine J.; Soucy, Geneviève; Tripathi, Monika; Upton, Melissa P.; Vieth, Michael; et al.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the clinical differences between carcinomas arising slightly above, slightly below, and within the gastroesophageal junction (GEJ); information provided by biopsies; information provided by resection specimens following neoadjuvant therapy; histologic differences existing between carcinomas arising slightly above, slightly below, and within the GEJ; differences provided by immunohistochemistry in these tumors; information given by endoscopic mucosal resection specimens; the role of esophageal pyloric gland adenomas as precursors of adenocarcinomas in the region of the cardia; the role of pancreatic metaplasia; Her2 immunoreactivity to make distinctions in the site of origin; and intestinal metaplasia limited to the cardia as a precursor of adenocarcinoma.